Functional characterization of gonococcal toxin-antitoxin systems - Bagabas, Salwa S. (2024)
Neisseria gonorrhoeae is the causative agent of the sexually transmitted infection, gonorrhoea. Gonorrhoea is a global health problem and one of the most common sexually transmitted infections in the world. Antibiotic resistance in N. gonorrhoeae is a growing problem, and in order to overcome this, it is necessary to develop preventative vaccines or novel treatments. Bacteria have evolved toxin-antitoxin (TA) systems to protect themselves from stressful conditions. TA systems have been linked to various functions including persister cell formation, biofilm formation, phage resistance and stabilisation of genetic elements. Previous work using the Toxin-Antitoxin DataBase (TADB) revealed the presence of three chromosomally-encoded type II TA systems (HicAB, MazEF, VapBC/FitAB) in N. gonorrhoeae strain FA1090. These were hypothesised to play an important role in the lifestyle of this human-restricted pathogen. In addition, exploitation of one or more of gonococcus TA systems could lead to novel treatment interventions. In this study, further bioinformatics analysis using PubMLST.org examined the prevalence and conservation of the TA systems across isolates. The FitAB, MazEF (and to a lesser extent the HicAB) TA systems were very highly prevalent and conserved across over 5000 N. gonorrhoeae isolates examined. To provide experimental confirmation that the predicted TA systems could influence bacterial growth, DNA fragments corresponding to fitA, fitB and both genes were amplified from N. gonorrhoeae FA1090, ligated into an arabinose-inducible expression plasmid and transformed into E. coli. Qualitative and quantitative growth assays utilizing these strains, along with previously engineered strains harbouring hicAB and mazEF constructs, revealed a lack of FitB or MazF-mediated toxicity in E. coli. In contrast, a HicA-mediated growth arrest effect, which could be abolished by co-expression of HicB, was detected, thus providing confirmation that the N. gonorrhoeae FA1090 genes, NGO1627/1628, encode a functional HicAB TA system. Subsequently, the HicA residues His24, His29, or His40, respectively, were changed to alanine residues by site-directed mutagenesis. Quantitative growth analysis confirmed that the His24 and His29 residues, but not His40 of gonococcal HicA are required for toxicity.